Crime wave: the American homicide epidemic - Tuttle, James (New York University Press, 2025)
"Crime Wave examines the unprecedented increase in the homicide rate beginning in 2015, tracing the impact of trends in alcohol consumption, drug abuse, firearm access and protests against police brutality"--